2005
DOI: 10.1063/1.1864232
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of p-type conductivity in nanocrystalline BaTiO3 ceramics

Abstract: Undoped BaTiO 3 ceramic samples with an average grain size of ϳ35 nm were prepared and the electrical properties investigated. The defect structure is dominated by acceptor impurities; therefore, the conductivity of nanocrystalline BaTiO 3 is of p-type. Comparing with microcrystalline BaTiO 3 , the conductivity of nanocrystalline BaTiO 3 is about 1 to 2 orders of magnitude higher and the activation energy remarkably lower, which is ascribed to a greatly reduced oxidation enthalpy in nanocrystalline BaTiO 3 ͑ϳ0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 19 publications
(12 reference statements)
1
36
0
1
Order By: Relevance
“…Conductivities of a variety of functional materials could be manipulated for fundamental research and application. [12][13][14][15][16] Size reduction decreases bulk parts and increases interfacial contributions. When the size is reduced further such that the interfacial regions interfere (e.g., overlap of space-charge regions), mesoscopic situations occur, which may eventually lead to new artificial crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Conductivities of a variety of functional materials could be manipulated for fundamental research and application. [12][13][14][15][16] Size reduction decreases bulk parts and increases interfacial contributions. When the size is reduced further such that the interfacial regions interfere (e.g., overlap of space-charge regions), mesoscopic situations occur, which may eventually lead to new artificial crystals.…”
Section: Introductionmentioning
confidence: 99%
“…In order to realize p-type conductivity in, e.g., SrðBa; CaÞTiO 3 , substitution of Ti-cations with several acceptor-type ions, such as Al 3þ ; Sc 3þ , etc., have been attempted in the past. 19,20 Unfortunately, it was found that acceptor-type dopants are compensated by the oxygen vacancies or protons 21 rather than by electron vacancies in the valence (oxygen 2p) band. At the same time, it does not seem to be very challenging to inject holes into the Eu 2þ valence band by alloying EuTiO 3 with, e.g., EuScO 3 .…”
mentioning
confidence: 98%
“…Up to three semicircles are usually observed in the Nyquist plot (grain, grain boundary and electrode contributions). However, nanocrystalline materials often exhibit just one semicircle in the frequency range typical of electrochemical impedance measurements, unless there is a significant electrode contribution (charge transfer resistance) [29].…”
Section: Conductivity Measurementsmentioning
confidence: 99%